2019
DOI: 10.1186/s12889-019-6935-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and risk factors of primary open-angle glaucoma - a cohort study based on longitudinal data from a German public health insurance

Abstract: Background This study estimates the prevalence and incidence rates of primary open -angle glaucoma (POAG) as well as risk factors based on a dataset from the largest German health insurance company. Methods A random sample of 250,000 persons at age 50+ of the Allgemeine Ortskrankenkasse (AOK) from 2010 to 2013 was used. Selected risk factors of POAG incidence were analyzed using multivariate Cox proportional hazard models. Results The age-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 54 publications
4
61
0
9
Order By: Relevance
“…Even greater prevalence rates in the elderly were reported in people of African descent-11% in those aged over 80 years in the Baltimore Eye Survey [37], 23.2% in the patients over 75 years of age in the Salisbury Eye Evaluation Glaucoma Study [94], and 24.8% in the male population aged 80 to 86 years in the Barbados Eye Study [93]. Additionally, a recent database analysis study confirmed a strong relationship between age and the prevalence of POAG, however, the incidence rates increased until the age of 85-89 years, and then slightly decreased in those over 90 years of age [95].…”
Section: Agementioning
confidence: 94%
“…Even greater prevalence rates in the elderly were reported in people of African descent-11% in those aged over 80 years in the Baltimore Eye Survey [37], 23.2% in the patients over 75 years of age in the Salisbury Eye Evaluation Glaucoma Study [94], and 24.8% in the male population aged 80 to 86 years in the Barbados Eye Study [93]. Additionally, a recent database analysis study confirmed a strong relationship between age and the prevalence of POAG, however, the incidence rates increased until the age of 85-89 years, and then slightly decreased in those over 90 years of age [95].…”
Section: Agementioning
confidence: 94%
“…Glaucoma is a leading cause of blindness and is generally asymptomatic until late in the disease, therefore early diagnosis an essential part of the control strategy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Primary open angle glaucoma (POAG), a frequent type of glaucoma worldwide, is a complex characterized by the progressive permanent degeneration of retinal ganglion cell (RGCs) death and distinctive visual field loss [1,2]. Regarding disease etiology, multiple risk factors, such as age [3,4], elevated intraocular pressure (IOP) [5,6], family history [7], and ethnic background [8], have been established in connection with the risk of POAG. In addition to these risk factors, genetics has also been shown to play a key role in the pathogenesis of POAG [9][10][11].…”
Section: Introductionmentioning
confidence: 99%